Research on Sparse Code Multiple Access Detection Technology in Satellite Communication Systems - Yiting JIANG; Lidong ZHU (天地一体化信息网络)
SCMA detection algorithms in the satellite communication system was studied,and optimal allocation of codebook and the incomplete iterative MPA detection algorithm were combined to improve system performance while reducing system complexity.The convergence of the SCMA detection algorithm was studied,and an improved serial-parallel MPA algorithm was proposed.This algorithm could accelerate the system convergence speed while reducing the processing delay,and the system complexity was also reduced.